Genetic divergence analyses in tef (Eragrostis tef (Zucc.) Trotter) landraces based on morpho-agronomic traits - Ashagrie, Siraye; Worede, Fisseha; Tarekegne, Wossen (Journal of Scientific Agriculture, 2022)
Tef (Eragrostis tef (Zucc.) Trotter) is a gluten-free cereal crop mainly grown in Ethiopia. Knowledge of the nature and magnitude of variation that exists in breeding materials is of great importance for effective breeding. This study was designed to assess the genetic divergence of tef landrace collections using quantitative and qualitative traits and to investigate the important trait in discriminating the tef landraces. The experiment was carried out at Adet Agricultural Research Center during the rainy season in 2019. Sixty-two landraces and two improved varieties were laid out in an 8×8 simple lattice design. Data were collected on 12 quantitative and three qualitative traits. The analysis of variance detected significant (P≤ 0.05) variation for panicle length and biomass yield, and highly significant (P≤ 0.01) differences among the tef landraces for the rest 10 traits, indicating the existence of appreciable genetic diversity that can be exploited in future tef breeding programs. Cluster analysis using the average linkage method grouped the 64 tef genotypes into four clusters. The highest inter-cluster distance was recorded between clusters III and IV; as a result, the tef genotypes from these clusters could be used as parents for future crossing programs. Principal components analysis revealed that the first four principal component axes accounted for 75.12% of the total variation among landraces, indicating that the traits considered were appropriate to detect the variation. The finding also demonstrated that grain yield, harvest index, days to heading, culm length and lodging index are higher contributors to the diversity of the tef landraces. These traits were most important in the discrimination of the landraces. Overall, the present study confirmed the presence of substantial diversity among the tef landraces.